Pendampingan Pembukuan Usaha Mikro, Kecil, dan Menengah di Desa Kerinjing - Luk Luk Fuadah; Kencana Dewi; Yulia Saftiana; Umi Kalsum (Yumary: Jurnal Pengabdian kepada Masyarakat, 2022)
Purpose: The purpose of this service is to provide assistance regarding Bookkeeping for Micro, Small and Medium Enterprises (MSMEs) in Kerinjing Village, Ogan Ilir. This is because it is important for MSME owners to understand the way and process of doing bookkeeping. Method: The method used in this service is conducting training / counseling and mentoring through monologues and also dialogues for MSME owners in Kerinjing Village. Implementation time is on 16, 23 and 30 September 2021. Participants who follow are all MSME owners in Kerinjing Village, Ogan Ilir. including the business of convection, culinary, souvenirs and stalls. Results: The results of this service are expected to be able to understand and know the bookkeeping process that can be utilized by MSMEs. Training/counseling and mentoring provide convenience for MSME owners in Kerinjing Village, Ogan Ilir. to process the book Conclusions: this training/instruction provides benefits and knowledge about tax incentives for MSMEs in Kerinjing Village, Ogan Ilir. Thus, the role of MSMEs owners is to carry out bookkeeping properly and correctly so that they can improve their ability to compete and also avoid fraud.